Robust Synthesis of Gold Nanotriangles and their Self‐Assembly into Vertical Arrays. Issue 6 (11th June 2019) - Szustakiewicz, Piotr; González‐Rubio, Guillermo; Scarabelli, Leonardo; Lewandowski, Wiktor
Abstract: We report an efficient, seed‐mediated method for the synthesis of gold nanotriangles (NTs) which can be used for controlled self‐assembly. The main advantage of the proposed synthetic protocol is that it relies on using stable (over the course of several days) intermediate seeds. This stability translates into increasing time efficiency of the synthesis and makes the protocol experimentally less demanding ('fast addition' not required, tap water can be used in the final steps) as compared to previously reported procedures, without compromising the size and shape monodispersity of the product. We demonstrate high reproducibility of the protocol in the hands of different researchers and in different laboratories. Additionally, this modified seed‐mediated method can be used to produce NTs with edge lengths between ca. 45 and 150 nm. Finally, the high 'quality' of NTs allows the preparation of long‐range ordered assemblies with vertically oriented building blocks, which makes them promising candidates for future optoelectronic technologies. Abstract : Easy nanotriangles ! Spherical seeds with high stability are shown as efficient starting materials for the synthesis of gold nanotriangles. The protocol is highly reproducible, allows to achieve nanotriangles with tunable sizes and plasmonic properties. Vertical assemblies of nanotriangles are achieved.